Low-Voltage SEM of Natural Plant Fibers: Microstructure Properties (Surface and Cross-Section) and their Link to the Tensile Properties. (2017) - Hamad, Sameer F.; Stehling, Nicola; Holland, C.; Foreman, J.P.; Rodenburg, C.
Abstract: In this study, the microstructure of different natural plant fibers (flax, jute, ramie, and sisal fibers) were characterized by using low-voltage Scanning Electron Microscopy (LV-SEM). The LV-SEM observations indicated that jute and sisal fibers exhibit less variation in terms of the fiber cross-sectional area, internal lumen shape and size, and cell wall thickness in comparison to flax and ramie fibers. We find that this is also reflected in the tensile properties of the fibers. The tensile properties of single ramie fibers and their fracture behavior was investigated in detail. The stress-strain behavior showed two distinctive regimes. For linear curves, the tensile strength varies from 648-1086 MPa whereas nonlinear curves result in much lower values (177-452) MPa. This variation was linked to differences in the microstructure of the fibers. The LV-SEM of the tensile fracture surfaces of ramie fibers revealed details on the cell wall structure and its fracture behavior under tensile load. Moreover, the SEM images confirm that the collapse of the primary cell wall generally leads to a non-linear stress-strain curve for single ramie fibers.